2011
DOI: 10.1007/s10661-011-2154-z
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the sedimentary carbon in an artificially disturbed deep-sea sedimentary environment

Abstract: An area of 0.6 km(2) in the manganese nodule field of the Central Indian Basin was physically disturbed and sediments discharged in the near bottom waters to simulate seabed mining and study its impact on benthic ecosystem. An estimated 2 to 3 tonnes of sedimentary organic carbon (C(org)) was resuspended into the water column during a 9-day experiment. The majority of the sediment cores from within the disturbed area and areas towards the south showed a ~30% increase in C(org) content as well as an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
(45 reference statements)
0
14
0
1
Order By: Relevance
“…Reasons for degradation of the marine environment include drifting sediment plumes and low frequency noise propagation, which could alter species distributions, ecosystem functioning or even seemingly unconnected processes such as carbon cycling (Nath et al, 2012;Le et al, 2017).…”
Section: Biodiversity Loss and The Potential For Habitat Recoverymentioning
confidence: 99%
“…Reasons for degradation of the marine environment include drifting sediment plumes and low frequency noise propagation, which could alter species distributions, ecosystem functioning or even seemingly unconnected processes such as carbon cycling (Nath et al, 2012;Le et al, 2017).…”
Section: Biodiversity Loss and The Potential For Habitat Recoverymentioning
confidence: 99%
“…The mining of manganese nodules on the seafloor produces sediment plumes and disperses resuspended sediment particles into the water column, resulting in a number of potential impacts on the marine environment and ecosystem (e.g., Jumars 1981;Sharma et al 2001;Khripounoff et al 2006;Nath et al 2012). One of the direct effects is an increased contribution to the sinking particle flux from resuspended sediment during the disturbance period.…”
Section: Development Of Indicator For Sediment Resuspensionmentioning
confidence: 99%
“…Mining operations discharge resuspended sediment into the water column that inevitably disturbs the marine environment (Khripounoff et al 2006;Nath et al 2012). The impact on the marine ecosystem is thought to depend mainly on the scale of disturbance and the amount of resuspended sediment (Hyun et al 1998;Sharma et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The CIB is a large abyssal basin, which is rich in ferromanganese nodules and bounded by ridges on three sides and is open to sediment input from the Bay of Bengal in the north‐east (see Nath et al, ). The past studies on the CIB sediments have reported total P (P total ) content (Banakar et al, ; Pattan & Jauhari, ), related sedimentary P to explain the calcium‐bearing phases (Nath et al, ) or have used organic C to P relation to assess the recovery of benthic ecosystem after a disturbance experiment (Nath et al, ). However, the processes that control P diagenesis and quantitative estimates of diffusive fluxes and P fractionation in chemically separable phases are not known.…”
Section: Introductionmentioning
confidence: 99%